Diagnosis of Female Urethral Cancer Based on Multimodal Ultrasound: A Case Report - Wang M; Chen W; He Y; Xu J; Zheng S; Wu M (International Journal of Women's Health, 2025)
Minfang Wang, Wanjun Chen, Ying He, Ji Xu, Shasha Zheng, Meng Wu Department of Ultrasound, The Affiliated People’s Hospital of Ningbo University, Ningbo, Zhejiang, People’s Republic of ChinaCorrespondence: Minfang Wang, Department of Ultrasound, The Affiliated People’s Hospital of Ningbo University, No. 251, Baizhang East Road, Yinzhou County, Ningbo, Zhejiang, 315040, People’s Republic of China, Tel +86-13484218486, Email wang11490432@163.com Meng Wu, Department of Ultrasound, The Affiliated People’s Hospital of Ningbo University, No. 251, Baizhang East Road, Yinzhou County, Ningbo, Zhejiang, 315040, People’s Republic of China, Tel +86-13586696417, Email Wm800214@126.comAbstract: While histopathology remains the diagnostic gold standard for urothelial carcinoma, this case highlights the emerging role of advanced ultrasonographic techniques in characterizing urethral malignancies. We present a 51-year-old female with a one-month history of refractory lower urinary tract symptoms (urinary frequency, urgency, dysuria, and nocturia) unresponsive to conventional anti-inflammatory therapy. Multimodal ultrasonographic evaluation, incorporating conventional sonography, transrectal ultrasound, elastography, and contrast-enhanced ultrasonography (CEUS), revealed a complex proximal urethral mass with malignant features. Subsequent cystoscopic and histopathological examinations confirmed the diagnosis of primary urethral adenocarcinoma. This case underscores the diagnostic value of comprehensive ultrasound protocols in evaluating female urethral neoplasms.Keywords: multimodal ultrasound, transrectal biplane ultrasound, shear wave elasticity, contrast-enhanced ultrasonography, female urethral adenocarcinoma